The Seven great hymns of the mediaeval church - Nott, Charles Cooper (Benson collection of hymnals and hymnology, 1877)
The Celestial country. -- Die Irae. -- Mater Speciosa. -- Stabat Mater. -- Veni Sancte Spiritus. -- Veni Creator Spiritus. -- Vexila regis. -- The Alleluiatic sequence.